159k views
2 votes
Drag the system of equation to the point that represents the solution to the system.

See attachment

Drag the system of equation to the point that represents the solution to the system-example-1
User Shaheem
by
5.5k points

1 Answer

4 votes
solving of the system equation: 2x-y=-13 ⇒(1) and y=x+9 ⇒(2)
by substituting from (2) at (1)
2x-(x+9)=-13
2x-x-9=-13
x=-4 ⇒ substituting at (2) ∴ y = -4+9 = 5
The point that represents the solution to the system = (-4,5)
========================================================

solving of the system equation: 3x+2y=10 ⇒(1) and 6x-y=10 ⇒(2)
by multiplying equation (2) ⇒ 12x-2y=20 ⇒(3)
adding (1) and (3)
15 x = 30 ⇒ x=2
from equation (2) 6x-y =10 ⇒⇒⇒ y = 6x-10 =12-10=2
The point that represents the solution to the system = (2,2)
=======================================================

solving of the system equation: 4x-3y=5 ⇒(1) and 3x+2y=-9 ⇒(2)
solve for x, y
we find x=-1 and y=-3

The point that represents the solution to the system = (-1,-3)
=======================================================

solving of the system equation: x+y=7 ⇒(1) and x-y=-1 ⇒(2)
adding (1) and (2)
2x=6 ⇒⇒⇒ x = 3
substitute at (1)
y =7-x=7-3=4
The point that represents the solution to the system = (3,4)
=======================================================

solving of the system equation: y=3x-7 ⇒(1) and y=2x-5 ⇒(2)
equating (1) and (2)
solve for x and y
we find x=2 ⇒⇒⇒ y = -1
The point that represents the solution to the system = (2,-1)
=======================================================

The system equation : y = 6 and x =-5
The point that represents the solution to the system = (-5,6)
=======================================================
The attached figure represent a conclusion for the answer

Drag the system of equation to the point that represents the solution to the system-example-1
User Pdexter
by
5.5k points